Effectiveness of Using E-learning at STEM-based Physics Learning to Improve Communication Skills of High School Students - Kristylia Sury; Ketang Wiyono; Sardianto Markos Siahaan (Universitas Lambung Mangkurat, 2022)
This study aims to determine the effectiveness of e-learning in STEM-based physics instruction on students' communication abilities. This research is a continuation of development research using the Allesi and Trollip model, which three experts have validated to make STEM-based e-learning to improve students' communication skills feasibly. The pre-experimental pretest-posttest design was used in this study's methodology. Thirty-one students from class XI MIPA Senior High Schools made up the sample for this study. The instrument used is a communication skill observation sheet with three observers to compare the impact before-after intervention, this study employed SPSS 25 to conduct a t-test and n-Gain. The results of the t-test and n-gain calculations show that STEM-based physics learning e-learning can significantly improve students' communication skills with an average n-gain score of 0.62 in the medium category. The highest increase was in oral communication (n-gain: 0.74), and the lowest was in student presentation skills (n-gain: 0.51). Furthermore, given the value of the t-count<t-table is 29.75<1.70, the analysis utilizing the t-test yields H1 being accepted so that the developed e-learning can be used as a medium for learning physics in the revolutionary era 4.0 in order to be able to face the demands of 21st-century learning.